Diffusing Capacity for Carbon Monoxide Predicts Response to Balloon Pulmonary Angioplasty in Patients With Inoperable Chronic Thromboembolic Pulmonary Hypertension - Li, Xin; Zhang, Yi; Luo, Qin; Zhao, Qing; Zeng, Qixian; Yang, Tao; Jin, Qi; Yan, Lu; Duan, Anqi; Liu, Jiaran; An, Chenhong; Ma, Xiuping; et al. (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background The hemodynamic results of balloon pulmonary angioplasty (BPA) varied among patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH). Previous studies revealed that microvasculopathy accounted for residual PH after pulmonary endarterectomy, which could be reflected by diffusing capacity for carbon monoxide (DLCO). We aim to identify whether DLCO could predict BPA response. Materials and Methods We retrospectively analyzed 75 consecutive patients with inoperable CTEPH who underwent BPA from May, 2018 to Jan, 2021 in Fuwai Hospital. According to hemodynamics at follow-up after the last BPA, patients were classified into “BPA responder” (defined as a mean pulmonary arterial pressure≤30 mmHg and/or a reduction of pulmonary vascular resistance≥30%) or “BPA non-responder”. Results At baseline, BPA responders had significantly higher DLCO than non-responders, although other variables were comparable. In BPA responders, DLCO decreased after the first BPA session and then returned to a level similar to baseline at follow-up. Conversely, DLCO increased constantly from baseline to follow-up in nonresponders. Multivariate logistic analysis showed that baseline DLCO<70% and the percent change of DLCO between baseline and after the first BPA session (ΔDLCO) >6% were both independent predictors of unfavorable response to BPA. Receiver operator characteristic analysis showed that the combination of baseline DLCO<70% and ΔDLCO>6% demonstrated a better area under the curve than either of these two variables used alone. Conclusions Baseline DLCO<70% and ΔDLCO>6% could independently predict unfavorable response to BPA. Measuring DLCO dynamically facilitates identifying patients who might have unsatisfactory hemodynamic results after BPA.